KITAB AL-MANAM - SUGIYANTO SUGIYANTO (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
This paper tries to study an edition of Ibn Abi Dunya's work, entitled Kitab al-Manam, edited by Leah Kinberg. This paper also aims to deal with the nature of Islamic classical texts and tries to examine the existing edited form of the text that can be scientifically accepted in recently scholarly circumstances. Kitab al-Manam is one of which has attracted many scholars due to its popular contents about dream. It is a collection of 350 narratives. Most of these narratives tell readers about information transmitted through dream. The nature of dream is very dominant in the whole of its content, nearly 327 narratives. Kinberg explains in the beginning of her edition that those dreams are mostly short and follow a set of basic patterns, which is common patterns in relating dreams: 'motifs and formulae·. Viewed from its main nature, Kitab al-Manam, as a whole, is a compilation of traditions drawn from early sources prior to Ibn Abi Dunya’. Somehow, this was an important work since that we hardly can find explanations about dreams prior to Ibn Abi Du'nya’. That's why, the populariry of Ibn Abi Du'nya’ was later acknowledged by many scholars especially those concerned with the nature of dreams in Islamic eschatology. Key Words: Kitab al-Manam, Ibn Abi Du'nya', dreams, critical edition